MAX phases and ultra-high temperature ceramics for extreme environments - Low, It-Meng; Sakka, Y. 1955-; Hu, C. F. 1980- (Research essentials., 2013)
"This book investigates a new class of ultra-durable ceramic materials, which exhibit characteristics of both ceramics and metals, and will explore recent advances in the manufacturing of ceramic materials that improve their durability and other physical properties, enhancing their overall usability and cost-effectiveness"--